Conductive Open‐Cell Silicone Foam for Tunable Damping and Impact Sensing Application - Rene Preuer; Jan Sleichrt; Daniel Kytyr; Philip Lindner; Umut Cakmak; Ingrid Graz (Macromolecular Materials and Engineering)
Abstract Nature has long served as a source of inspiration for the development of new materials, with foam‐like structures in citrus fruits such as oranges and pomelos serving as examples of efficient energy dissipation. Inspired by the internal structure of citrus fruit, soft conductive silicone foams are fabricated. The foams are made from a polydimethylsiloxane (PDMS) by mold casting using sugar templates. Addition of silicone oil and carbon black to the silicone allows creation of extremely soft foams that serve as resistive sensor. Completed by a pneumatic radial compression actuator (PRCA) surrounding the foams like a ring in analogy to citrus fruit peel, smart tunable dampers with sensing capabilities are demonstrated. The foams are evaluated for their electrical and mechanical properties alone as well as in conjunction with the PRCA. When pressurized, the PRCA radially compresses the smart foams, allowing to tune their stiffness and thus damping properties. Tunability of this system is evaluated by means of ball drop tests with respect to damping as well as the sensor performance regarding its sensitivity and stability. Overall, the study provides valuable insights into the behavior of conductive silicone foams and their potential as cushioning and impact sensing material.